If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10 = 64 + -1x Reorder the terms: 10 + 5x = 64 + -1x Solving 10 + 5x = 64 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 10 + 5x + x = 64 + -1x + x Combine like terms: 5x + x = 6x 10 + 6x = 64 + -1x + x Combine like terms: -1x + x = 0 10 + 6x = 64 + 0 10 + 6x = 64 Add '-10' to each side of the equation. 10 + -10 + 6x = 64 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = 64 + -10 6x = 64 + -10 Combine like terms: 64 + -10 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 3x^6+15x^4-12x^2=0 | | s-9=11 | | -5+4x+3x=-33 | | log(4)(x+2)=3 | | 4(-6+x)=16 | | 3(x+8)+5x=8x-24 | | 6(3x+8)=228 | | -6x+2y=34 | | 3(5x+9)=-37+19 | | 6(-9-x)=-24 | | 2(2x)=32 | | -8(8x-6)=-6x-228 | | -2x+2=7x+65 | | 7m(2m-12)=0 | | -1+6x=-3x+8 | | 2(4x+2)+9x= | | 50/x=3 | | 90=3x+5x-6 | | ln(x)-ln(4)=0 | | (7+5x)-5x= | | ln(x)-on(4)=0 | | -25=5(3g+4) | | (9x+10)+(13-9x)= | | 3x^2-2y^2=1 | | z-38=-28 | | 12(5x+9)-11x= | | 25x+7(1.50)=10 | | X^5x=6 | | 5-5x-x=53 | | -1+5x-7x=3 | | 8.4254+.6018R=R | | 6(x+2)=5(x+4) |